Implikasi perlaksanaan teknik sumbang saran terhadap kemiahiran penulisan karangan di kalangan pelajar di sekolah menengah all saints kota kinabalu sabah - Ali Zapar Ali (2005)
The purpose of this research is to identify the implication of the brainstorming implementation towards writing skill in Bahasa Melayu among the students of SM.All SAINTS, Kola Kinabalu Sabah. Besides, this research also aimed to gain information on how effective this technique in essay writing among the students of SMAll SAINTS. For this purpose, about 169 form one students represent six dasses to be the experimental sample. The students are going to be divided Into two groups, that is the Control and Experimental group. This group will be tested in Pre and Post test which will be handle by the form one Bahasa Melayu teachers within four weeks time for each test The Weirsma and Heaton Marking Scheme are being used for this research to gain the percentage score. There are rwe main structures In this instrument, the Grammar, Content, Vocabulary, Arrangement and Mechanise which has been divided Into 20 Items. The teachers who give the test will give the marks according to the 20 items given and will also give A,~l;D and E scale for the students achievement. The gained data will be analyse by using the Descriptive Statistic Method, Average Percentage and Excel to obtain the Increasing percentage. The result shows that the brainstorming technique Is w:'ty helpful and suitable for teaching essay writing. In the Pre and Post test for this Control and Experimental group proved that the level of achievement together with the average of percentage Is Increasing about 15.46%. The students writing skill improved a lot after the brainstorming technique Is emphasis on them. It means that this technique Is vety effective In teaching essay writing.